In situ study of electric‐field‐induced ferroelectric and antiferromagnetic domain switching in polycrystalline BiFeO3. Issue 4 (14th September 2018) - Liu, Lisha; Hinterstein, Manuel; Rojac, Tadej; Walker, Julian; Makarovic, Maja; Daniels, John
Abstract: Antiferromagnetic domain switching induced by ferroelectric polarization switching has previously been observed in situ in both multiferroic BiFeO3 single crystals and thin films. Despite a number of reports on macroscopic magnetoelectric measurements on polycrystalline BiFeO3, direct in situ observation of electric‐field‐induced antiferromagnetic domain switching in this material has not been addressed due to the lack of high‐quality samples capable of electrical poling. Here, the electric field control of antiferromagnetic domain texture is identified in polycrystalline BiFeO3 using in situ neutron diffraction, showing the resultant magnetic domain reorientation induced by an electric field. An antiferromagnetic domain reorientation to a value of 2.2‐2.5 multiples of a random distribution (MRD) is found to be induced by an electric field that provides a non‐180° ferroelectric‐ferroelastic domain texture of 2.2‐2.5 MRD along the field direction. The current results show well‐controlled coupling of multiferroic domain texturing in single‐phase polycrystalline BiFeO3 .